Exploring the Potential of High Value-Added Recycling of Wool Wastes with the Aid of Sustainable Process Design by DOZNTM - Byeolyi Choi; Soyun Jeong; Yaewon Park (Journal of Natural Fibers)
This study aimed to establish a sustainable framework for the chemical upcycling of wool waste by evaluating previously reported keratin extraction methods based on the DOZN™ sustainability score, material cost efficiency, and keratin yield. The reduction reaction with L-cysteine was selected, achieving a yield of 28–36% and a relatively low DOZN™ aggregate score of 12, compared to oxidation and reduction with dithiothreitol, which scored 29 and 16, respectively. This method successfully extracted keratin from various wool sources, including wool yarns, dyed wool sweaters, and blended wool sweaters. SEM and FTIR deconvolution analyses confirmed that the extracted keratin from all sources exhibited similar microstructures. A proof-of-concept demonstration showed that these keratins can be used in formulation additives, adsorptive gels, and biodegradable paper alternatives, with a notable biodegradability of 91% weight loss in 44 days. This research provides a framework for rationally designing textile waste recycling processes, considering both feasible applications and sustainability as assessed by the DOZN™ tool, which evaluates alignment with the 12 principles of green chemistry. By leveraging this framework, future research and industry collaborations can explore expanded applications of keratin-based materials and adopt sustainable practices, enhancing the efficiency and environmental sustainability of textile recycling processes.